1990
DOI: 10.1016/0375-9474(90)90003-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 11Li in the cluster-orbital shell model for the 9Li + n + n system

Abstract: The properties of '"Li are studied in detail in the cluster-orbital shell model assuming the structure of 'Li+n+n. The interactions acting between the constituent particles are carefully determined consistently with available data. Large and flexible bases for the valence neutrons are represented as a superposition of gaussian functions. The anomalously Iarge radius of "Li is nicely reproduced.The density dist~butions calculated clarify the picture of the neutron halo. The binding energy is, however, calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…For neutron halos the charge radius is expected to be the one of the core. Elastic electron scattering on 11 Li or 6 He will be important to confirm that this picture of neutron halo nuclei is correct. As one slightly increases the energy transfer to the nucleus the halo will break up, and coincidence (e, e ′ x) measurements can be made, with x either a halo neutron or the stable core.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…For neutron halos the charge radius is expected to be the one of the core. Elastic electron scattering on 11 Li or 6 He will be important to confirm that this picture of neutron halo nuclei is correct. As one slightly increases the energy transfer to the nucleus the halo will break up, and coincidence (e, e ′ x) measurements can be made, with x either a halo neutron or the stable core.…”
Section: Introductionmentioning
confidence: 92%
“…Very soon it was suggested that these nuclei could be understood as a core surrounded by one or more neutrons, which extend to several times the nuclear radius [5]. This picture was supported by subsequent studies that proved the validity of the few-body models as an appropriate method to describe the most general properties of halo nuclei [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations